Flow : the psychology of optimal experience. - Csikszentmihalyi, Mihaly, 1934- (New York : Harper Perennial, 2008)
Psychologist Mihaly Csikszentmihalyi's famous investigations of "optimal experience" have revealed that what makes an experience genuinely satisfying is a state of consciousness called flow. During flow, people typically experience deep enjoyment, creativity, and a total involvement with life. In this new edition of his groundbreaking classic work, Csikszentmihalyi demonstrates the ways this positive state can be controlled, not just left to chance. Flow: The Psychology of Optimal Experience teaches how, by ordering the information that enters our consciousness, we can discover true happiness and greatly improve the quality of our lives.